Diagnostic Effectiveness of Transforming Growth Factor Beta 1 in Assessing the Risk of Developing Graft Dysfunction in Liver Recipient Children - R. M. Kurabekova; O. M. Tsiroulnikova; I. E. Pashkova; A. G. Olefirenko; O. E. Gichkun; L. V. Makarova; R. A. Monakhov; P. O. Shevchenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The problem of non-invasive monitoring of the liver condition is particularly relevant in liver transplantation among young children. Transforming growth factor beta 1 (TGF-β1) is a pleiotropic cytokine with a profibrogenic and immunosuppressive effect that can have a definite effect on the liver transplant functioning.Aim. To determine the diagnostic efficacy of TGF-β1 in blood when assessing the risk of developing graft dysfunction in liver recipient children. Materials and methods. 95 children aged 3 to 73 months with liver cirrhosis of various etiologies were surveyed. All the patients underwent liver transplantation (LT) from a living related donor. The TGF-β1 concentration in plasma was determined using ELISA on average 3 ± 2 days prior to liver transplantation and in the early post-transplant period.Results. The level of TGF-β1 in the blood of children with liver cirrhosis was lower than in healthy children (p = 0.001). LT was accompanied by an increase in the TGF-β1 content in the blood of recipients (p = 0.001). The incidence of graft dysfunction in the early postoperative period correlated with the pre-transplantation level of TGF-β1 (r = 0.40, p = 0.00), which was lower in recipients with developed graft dysfunction than in patients without dysfunction (1.7 ± 1.3 ng/ml versus 6.7 ± 5.3 ng/ml, p = 0.001). The analysis of the test diagnostic efficiency showed that the area under the ROC curve (AUC) was 0.85 ± 0.05, 95 % CI 0.75–0.94, the sensitivity of the method was 83 %, its specificity was 77 %. When the marker value was less than the threshold (2.2 ng/ml), the relative risk of developing graft dysfunction was 11.4 ± 0.7, 95 % CI 2.7-48.7. The accuracy of the method, the positive predictive value and the negative predictive value of the results were 78, 83 and 77 %, respectively. Conclusion. The level of TGF-β1 in the blood of liver recipient children before transplantation below 2.2 ng/ml increases the risk of developing graft dysfunction in the early postoperative period 11-fold. Measuring the TGF-β1 level in the blood prior to liver transplantation makes it possible to identify recipients with 85 % chance of developing a graft dysfunction.